Dysmegakaryopoiesis in myelodysplastic syndromes (MDS): an immunomorphometric study of bone marrow trephine biopsy specimens. Issue 4 (April 1991) - Thiele, J; Quitmann, H; Wagner, S; Fischer, R
Abstract : An immunohistochemical and morphometric analysis was performed on trephine biopsy specimens of the bone marrow in 40 patients (23 men and 17 women, mean age 62 years) with different subtypes of myelodysplastic syndromes (MDS) to determine dysmegakaryopoiesis, but particularly precursor cells–that is, pro- and megakaryoblasts. In 31 of the 40 patients the numbers of megakaryocytes were increased which was associated with a predominance of smaller cell forms (micromegakaryocytes). Compared with periodic acid Schiff, immunostaining with a formalin resistant monoclonal antibody against glycoprotein IIIa (Y2/51(CD61) showed a clinically important proportion of immature elements. These could be designated pro- and megakaryoblasts by taking morphometric measurements on smears and bone marrow sections. There was a relevant increase in the number of promegakaryoblasts in 32 patients, consistent with uncontrolled expansion of the precursor pool. Seventeen repeated bone marrow biopsy specimens taken after chemotherapy largely showed a decrease in the numbers of megakaryocytes including the precursor cell population. Moreover, morphometric evaluation disclosed that micromegakaryocytes in MDS differ significantly from those in chronic myeloid leukaemia (CML) due to distinctive nuclear features and a disturbed nuclear:cytoplasmic ratio. These changes generate a more pleomorphic or atypical appearance of this cell population in MDS, compared with micromegakaryocytes in CML. It is concluded that the disproportionate increase in megakaryocyte precursors and the grossly abnormal aspects of micromegakaryocytes in MDS are characteristics of the severe defect involving haematopoiesis in this disorder.